2019
DOI: 10.13057/biodiv/d200932
|View full text |Cite
|
Sign up to set email alerts
|

Lectin histochemical study of the quill sebaceous gland in the dorsal skin of the Sunda porcupine (Hystrix javanica)

Abstract: Abstract. Prawira AY, Novelina S, Farida WR, Darusman HS, Agungpriyono S. 2019. Lectin histochemical study of the quill sebaceous gland in the dorsal skin of the Sunda porcupine (Hystrix javanica). Biodiversitas 20: 2677-2684. In the Sunda Porcupine skin, the sebaceous glands of the quill follicles are multi-lobed alveolar and better developed than those of hair follicles. Using lectin histochemistry, we have studied the distribution of sugar-binding in the sebaceous glands of quills in comparison with those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…They are also the dominant structure in the skin of the Sunda porcupine. Histological examination has shown that quill follicles are composed of connective tissue of various densities, an abundance of fat tissue, well‐developed sebaceous glands, erector muscles and an epidermal lining (Prawira et al, 2019; Prawira, Hanadhita, et al, 2018; Prawira, Novelina, et al, 2018). The arrangement of quill follicles, connective, erector and subcutaneous muscles in the skin play an important role in quill erection and contribute to the defence mechanism of the porcupine (Chapman & Roze, 1997; Zherebtsova, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…They are also the dominant structure in the skin of the Sunda porcupine. Histological examination has shown that quill follicles are composed of connective tissue of various densities, an abundance of fat tissue, well‐developed sebaceous glands, erector muscles and an epidermal lining (Prawira et al, 2019; Prawira, Hanadhita, et al, 2018; Prawira, Novelina, et al, 2018). The arrangement of quill follicles, connective, erector and subcutaneous muscles in the skin play an important role in quill erection and contribute to the defence mechanism of the porcupine (Chapman & Roze, 1997; Zherebtsova, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The fatty acid components from the porcupine's skin are present in the quills and have an antibacterial effect since they are obtained from the skin (Prawira et al, 2018). In addition, the sebaceous glands in porcupine quill follicles, which are oil glands, are reported to be significantly larger than hair oil glands (Prawira et al, 2019). The large size will release large amounts of oil into the porcupine quills so that oil and other lipids will be present on the surface of the quills and skin.…”
Section: Introductionmentioning
confidence: 99%
“…There is also no published study about the intestinal structure, but that of its distant relatives, such as the African porcupine (Hystrix africaeaustralis), has been studied by van Jaarsveld (1983), andvan Jaarsveld andKnight-Eloff (1984). Apart from its special skin characteristics due to the quill (Prawira et al 2018(Prawira et al , 2019(Prawira et al , 2022, the digestive system of Sunda porcupine needs to be studied to identify the morphological adaptation to the feeding diet. Therefore, this study aims to investigate the intestinal structure of the Sunda porcupine as an important part of its digestive system.…”
Section: Introductionmentioning
confidence: 99%